Pengaruh Model Pembelajaran Berbasis Masalah (PBM) Melalui Aplikasi Zoom Terhadap Berpikir Kritis dan Persepsi Siswa Dalam Pembelajaran IPA DI SMP Negeri 1 Ujan Mas: (The Effect of Problem-Based Learning Model (PBM) Through the Zoom Application on Students' Critical Thinking in Science Learning at SMP Negeri 1 Ujan Mas) - Tri Sutrisno; Irwandi Irwandi; Rusdi Hasan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The critical thinking ability of students in science learning is still low. This study aims to determine the effect of the problem-based learning model (PBM) through the zoom application on students' critical thinking in science learning at State Junior High Schools. The research method used in this research is Quasi Experiment. With pretest and posttest experimental group design. The population in this study were all seventh grade students of SMP Negeri 1 Ujan Mas in the 2020/2021 academic year with a sample of 2 classes, namely class VII.1 as a control class using conventional learning and class VII.2 as an experimental class using a problem-based learning model. , each class consists of 30 students. Collecting data using essay tests to measure students' critical thinking skills. The results showed that there was a significant effect from the application of the problem-based learning model through the zoom application on the critical thinking skills of SMP Negeri 1 Ujan Mas students and on students' perceptions that they were in the medium category. Abstrak. Kemampuan berpikir kritis siswa dalam pembelajaran IPA masih rendah. Penelitian ini bettujuan untuk mengetahui pengaruh model pembelajaran berbasis masalah (PBM) melalui aplikasi zoom terhadap berpikir kritis siswa dalam pembelajaran IPA Di SMP Negeri. Metode penelitian yang dilakukan dalam penelitian ini adalah Quasi Experimen. Dengan desain pretes dan postest experimental group design. Populasi pada penelitian ini adalah seluruh siswa kelas VII SMP Negeri 1 Ujan Mas Tahun Pelajaran 2020/2021 dengan sampel sebanyak 2 kelas yaitu kelas VII.1 sebagai kelas kontrol yang menggunakan pembelajaran konvensional dan kelas VII.2 sebagai kelas eksperimen yang menggunakan model pembelajaran berbasis masalah, masing-masing kelas berjumlah 30 siswa. Pengumpulan data menggunakan tes essay untuk mengukur kemampuan berpikir kritis siswa. Hasil penelitian menunjukkan terdapat pengaruh yang signifikan dari penerapan model pembelajaran berbasis masalah melalui aplikasi zoom terhadap kemampuan berpikir kritis siswa SMP Negeri 1 Ujan Mas dan pada persepsi siswa masuk kedalam kategori sedang.